Translanguaging und sein Potenzial für den DaF-Unterricht sowie fachsprachlichen DaF-Unterricht - Jazbec, Saša (Vestnik za tuje jezike, 2024)
Foreign language teaching, especially the teaching of non-English languages, is facing significant challenges today due to the status of English among languages and in the context of migration, globalization, and mediatization. The old, familiar methods that have long been successful with regard to language learning and teaching are now no longer effective, do not motivate learners, and do not achieve the results that teachers want. The current monolingual paradigm of foreign language teaching will thus have to change, and various different approaches are available. This paper focuses on translanguaging, a new approach to language processing and use that starts with the individual and their single linguistic repertoire. These resources can be understood from the perspective of translingualism as a transition be-tween languages or a fluid use of all available linguistic resources. This transition is essential in bridging the communication gap between the individual’s professional knowledge and limited foreign language skills, or overcoming the communication constraints caused by limited foreign language competencies. The first part of the paper discusses the concept of translingualism from a theoretical linguistic and didactic perspective. In the second part, the teaching of Tessa Brown, an American teacher who has been working successfully with the translingual approach, is described, and two didactic proposals for implementing translingualism in the classroom – namely the so-called translingual spaces and translingual rings – are presented. The first proposal illustrates a pedagogical experiment in which cross-linguistic transitions are essential for contextual diversity, even if developing foreign language competence or communicative skills in German needs to be addressed. The second proposal describes possible didactic methods in the classroom. We have theoretically identified and illustratively shown that the cross-linguistic approach has significant potential for teaching German as a foreign language, as well as for teaching German as a language for specific purposes.
Keywords: crossing between languages; čezjezični obroči; čezjezični prostori; foreign language learning; German as a foreign language; jeziki stroke; neangleščine; nemščina kot tuji jezik; Non-English languages; prehajanje med jeziki; translanguaging spaces